Penyelesaian Tindak Pidana Pencurian melalui Denda Adat Antang dan Mekau pada Masyarakat Dayak Bahau di Kampung Keliwai Kabupaten Kutai Barat - Maria Celi Hunyang; La Syarifuddin; Aryo Subroto (Eksekusi : Jurnal Ilmu Hukum dan Administrasi Negara, 2026)
This research is motivated by the existence of customary law as  a living law that is constitutionally  recognized and applied by the Dayak Bahau Community in Keliwai Village in solving the crime of theft. This practice prioritizes local wisdom and social balance through  the Antang and Mekau customary fine mechanism  as an alternative settlement outside the formal state criminal justice system. However, there are legal issues regarding the effectiveness of sanctions in providing a deterrent effect and protecting the rights of victims, especially vulnerable groups such as people with disabilities. The research uses socio-legal research methods  with a qualitative approach through in-depth interviews with traditional chiefs, victims' families, and community leaders. The results of the study show that the implementation of Antang (large urns) and Mekau (small urns) customary fines is carried out through customary deliberations led by the Customary Chief by involving the perpetrators, victims, and families. Philosophically, these fines function as a symbol of "village cleansing" (Ngaping Umaq) to restore the disturbed cosmic balance. Socially, this mechanism has proven to be effective in resolving conflicts and maintaining community harmony. However, the effectiveness of customary fines in terms of restoring victims' rights is considered not optimal. In certain cases, there is a significant gap between the value of the fine imposed and the real material losses suffered by the victim, so that the goal of restorative justice has not been fully achieved for the victim.